(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2004)
In recent years detailed sedimentological and biostratigraphical investigations have revealed Anisian terrestrial sediments in three sections of the Bükk Mountains. In the northern part of the mountains fluviatile sediments were recognised while in the southern part lake deposits were observed. Based on the stratigraphical position and microfacies analyses of the resedimented grains, two terrestrial events can be reconstructed. The age of the younger is late Pelsonian-early Illyrian?. This can be correlated with the Richthofen Conglomerate in the Dolomites. The age of the older terrestrial event could not be established exactly but it must have happened either in the Pelsonian or in the Aegean-Bithynian; consequently it may correlate either with the Voltago or with the Piz de Peres Conglomerate in the Dolomites. The terrestrial sediments in the Bükk Mountains are parts of a volcano-sedimentary succession, which is characteristic of the updoming part of a rifting area. Terrestrial sediments in the southern part of the mountains represent the deepest part of the half-grabens, which originated during the course of the rifting. The present paper gives an overview of the Anisian-Lower Ladinian terrestrial sediments in the Southern Alps-Dinarides and considers their formation during the Triassic rifting of the Vardar-Meliata branch of the Neo-Tethys.